Teaching Various Aspects of the Language and Forming Skills. Teaching Pronunciation.The Importance of Correct Pronunciation in Language Learning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article discusses methods of teaching various aspects of language and the formation of skills, the importance of correct pronunciation in language learning. Teaching speech activity, the development of oral speech in English in the classroom of modern technologies and methods of linguistics in modern English.